"Run it through me:" Positioning, power, and learning on a high school robotics team. Issue 4 (19th October 2020) - Hennessy Elliott, Colin
ABSTRACT: Background: Scholars have analyzed the possibilities that robotics-centered learning programs offer, including opportunities for developing collaboratively and engaging in authentic STEM professional practice. This work adds a sociopolitical perspective, explicating a case of a newcomer to a robotics team that elucidates the nuances of in-the-moment social positioning and its enduring impact on youth's participation in afterschool STEM learning environments. Methods: Through interaction analysis of three episodes and ethnographic perspectives, participants' contributions to social interaction are analyzed as chronotopes, or spacetime representations, to understand how Denisse's, a young Black and Latinx woman, role as the driver of the team's robot at competitions is collaboratively crafted, building on the feminist tradition of positioning theory. Findings: My analysis shows that Denisse is both empowered, through co-production of future decision-making in practice, and disempowered, through the rejection of non-present spacetime storylines at the competition. Further, notions of expertise and ownership are brought to bear on interactions, together with racialized and gendered narratives across the negotiations of the role of the driver to limit Denisse's local social power. Contribution: This story shares how representation is not enough for educational justice for minoritized youth and informs how STEM education communities must take on the task, together.